Creation of gallium acid and platinum metal sites in bifunctional zeolite hydroisomerization and hydrocracking catalysts by atomic layer deposition. Issue 6 (11th February 2020) - Geerts, Lisa; Ramachandran, Ranjith K.; Dendooven, Jolien; Radhakrishnan, Sambhu; Seo, Jin Won; Detavernier, Christophe; Martens, Johan; Sree, Sreeprasanth Pulinthanathu
Abstract : Active sites in bifunctional zeolite catalysts were engineered using atomic layer deposition (ALD). Gallium acid and platinum metal sites were introduced to zeolites via ALD and investigated for a hydroconversion reaction. Abstract : Atomic layer deposition (ALD) is a vacuum technology for the deposition of a small number of atoms on surfaces. Its use in catalysis is growing. Here, we explored the use of ALD for introducing acid and metal sites in zeolites for performing bifunctional catalysis. Plasma-enhanced ALD involving cyclic exposure of a sample to tris(2, 2, 6, 6-tetramethyl-3, 5-heptanedionato)gallium (Ga(TMHD)3 ) vapor and O2 plasma (Ga-ALD) was used for introducing acid sites. Interestingly, Ga-ALD was found to cause preferential deposition of Pt nanoparticles via incipient wetness impregnation on the edges of COK-14 crystal plates, in contrast to previously published results on Al-ALD. Benefiting from the optimum proximity between the Ga acid and Pt metal sites, it is shown here that Ga-ALD is a way to introduce sufficient acidity into all-silica zeolite COK-14 for obtaining bifunctional catalytic behavior. Hydrogenation–dehydrogenation activity in bifunctional catalysts is typically provided by trace amounts of platinum dispersed on the zeolite. Pt-ALD was applied for finely dispersing platinum on ZSM-5 zeolite. Pt-ALD involved alternating exposure to the trimethyl(methylcyclopentadienyl)platinum(iv ) (MeCpPtMe3 ) precursor and ozone. The Pt-ALD method proved to be an efficient way to uniformly disperse ultra-small Pt nanoparticles onto the zeolite. The bifunctional catalytic behavior of ALD-functionalized zeolites was confirmed in the hydroconversion of the n -decane model molecule.